2018
DOI: 10.31327/jee.v3i2.860
|View full text |Cite
|
Sign up to set email alerts
|

Writing Material for Office Administration Study Program in Vocational High School: Students’ Need Analysis

Abstract: Vocational High School is course with aim to prepare the students to have specific skills by having practical activities based on its study program. It has the same purpose with English for specific purposes (ESP) course which aims to meet the students’ specific language need. ESP courses help students to use English appropriately as well as accurately to perform their jobs in a various situations where they encounter their English language function. ESP course often begins with the students’ need. Students’ n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous research did not explore this. The present study also different with the result found by several researcher in different fields such as needs of learning material by (Yolanda et al, 2018), needs analysis on teaching and learning (Alfian, 2019) needs analysis in ESP (Istiningrum, 2022), English Language Training Need Analysis for Engineering Students (Clement & Murugavel, 2015) and Students' Need for Developing Material of English for Civil Engineering (Wulanjani, 2018).…”
Section: Findings and Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Previous research did not explore this. The present study also different with the result found by several researcher in different fields such as needs of learning material by (Yolanda et al, 2018), needs analysis on teaching and learning (Alfian, 2019) needs analysis in ESP (Istiningrum, 2022), English Language Training Need Analysis for Engineering Students (Clement & Murugavel, 2015) and Students' Need for Developing Material of English for Civil Engineering (Wulanjani, 2018).…”
Section: Findings and Discussioncontrasting
confidence: 96%
“…Several researchers have conducted studies on the needs of learners. Needs of learning material by (Yolanda, Ngadiso, & Sumardi, 2018), needs analysis on teaching and learning (Alfian, 2019) need analysis in ESP (Istiningrum, 2022), English Language Training Need Analysis for Engineering Students (Clement & Murugavel, 2015) and Students' Need for Developing Material of English for Civil Engineering (Wulanjani, 2018). In this study, the researcher elaborates on the Students' Learning and Language Needs in General English Courses in the Civil Engineering Study Program.…”
Section: Introductionmentioning
confidence: 99%
“…Other research conducted by Yolanda, Ngadiso, and Sumardi [18] revealed that the Vocational High School attempts to strengthen the students' specific language abilities to the requirements of the target industry. The learning objectives are for students can handle and compose letters, documents, and reports.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that attempt to elucidate additional facets of a textbook include the following. Yolanda (2018), Inderawati, Petrus, Eryansyah, & Meilinda (2021), Akbarjono, Melati, Martina, Syafryadin (2021) and Ali, Javed, & Murtaza (2020) used certain criteria to identify the strengths and limitations. Additionally, Miroud (2021) evaluated the reading material to ascertain the textbook's content.…”
Section: Introductionmentioning
confidence: 99%